Determinants of Current Account Deficits in Developing Countries - Loayza, Norman, 1964- 1964- (The World Bank, 1999)
July 2000 - In developing countries, increases in current account deficits tend to be associated with a rise in domestic output growth and shocks that increase the terms of trade and cause the real exchange rate to appreciate. Higher savings rates, higher growth rates in industrial economies, and higher international interest rates tend to have the opposite effect. Calderón, Chong, and Loayza examine the empirical links between current account deficits and a broad set of economic variables proposed in the literature. To accomplish this, they complement and extend previous research by using a large, consistent set of macroeconomic data on public and private domestic savings, external savings, and national income variables; focusing on developing economies by drawing on a panel data set for 44 developing countries and annual information for the period 1966-95; adopting a reduced-form approach rather than holding to a particular structural model; distinguishing between within-country and cross-country effects; and employing a class of estimators that controls for the problems of simultaneity and reverse causation. Among their findings: · Current account deficits in developing countries are moderately persistent. · A rise in domestic output growth generates a larger current account deficit. · Increases in savings rates have a positive effect on the current account. · Shocks that increase the terms of trade or cause the real exchange rate to appreciate are linked with higher current account deficits. · Either higher growth rates in industrial economies or higher international interest rates reduce the current account deficit in developing economies. This paper-a product of the Regional Studies Program, Latin America and the Caribbean Region-is part of an effort in the region to understand the determinants of external sustainability. The authors may be contacted a++